Using Cooperative Activity in Forming Students' Learning Culture - Abdullayevna, Khaitova Firuza (International Journal on Human-Computing Studies, 2023)
this article discusses the use of cooperative activities of schools, parents, and libraries in the formation of the reading-reading culture of students in primary grades. In the process of working with parents and librarians, class leaders and subject teachers in the organization of cooperative activities in the formation of the reading culture of students, it is explained that the activities, quizzes, various competitions are an important factor in the development of the reading culture of students. Classroom teachers, science teachers, elementary school teachers and librarians work together with parents to conduct collaborative activities. During the classes, the teacher creates conditions that stimulate the reading activity of students, constantly changes the methods of its application, invites local writers, the methodology of these classes allows each student to have an organized interaction with the book. based on.